Shear Motion Characteristics Analysis of Electrorheological Fluids Between Flat Disk and Corrugated Disk - Li, Chunyu; Chen, Bingsan; Huang, Yijian (Frontiers in Materials, 2022)
In order to improve the transmission torque caused by the electrorheological effect, a corrugated disk is proposed to replace the traditional flat disk by changing the electrode surface shape. The new mechanism puts the device in a shear-squeeze mode of operation. Based on the constitutive equation of the electrorheological fluids (ERFs), the shear motion characteristics of the ERFs between the flat disk and the corrugated disk are analyzed, including the pressure distribution, torque equations, and the comparison with double-flat-disk mechanism. The analysis shows that compared with the double-flat-disk structure, the flat-disk-corrugated-disk structure can enhance the torque transmitted 2.6 times under the same operating parameters. The magnification of the torque has nothing to do with the curve number of the corrugated disc, and mainly depends on the structural parameters of the device and corrugations and the characteristic parameters of the electrorheological fluid. It is proved that the mechanism can provide new ideas and new methods for the engineering application of electrorheological transmission technology.